Electrocautery ablation therapy for anal intraepithelial carcinoma: A study protocol. Issue 51 (23rd December 2022) - Ando, Naokatsu; Mizushima, Daisuke; Takano, Misao; Kitamura, Hiroshi; Shiojiri, Daisuke; Nakamoto, Takato; Aoki, Takahiro; Watanabe, Koji; Uemura, Haruka; Gatanaga, Hiroyuki; Oka, Shinichi
Abstract : Background: Anal cancer is a human papillomavirus-related cancer. Screening with high-resolution anoscopy (HRA) and subsequent therapeutic intervention are increasingly recognized as the standard procedure for anal cancer. Generally, lesions suspected as being high-grade squamous intraepithelial lesions are biopsied and treated if they are grade 2 or 3 anal intraepithelial neoplasia (AIN). According to several studies, electrocautery ablation for grade 2 or 3 AIN is highly effective. However, relapse within and outside the targeted areas after the intervention is a clinical problem. In Japan, electrocautery ablation is not available at most facilities. Therefore, this study aims to investigate the efficacy and safety of electrocautery ablation. Methods: This single-arm, open-label, pilot intervention study will investigate the efficacy and safety of electrocautery ablative therapy using high-frequency medical devices. Patients diagnosed with grade 2 or 3 AIN will be included and will receive ablation treatment. Then, they will be followed up at 3 and 6 months after the procedure for HRA-guided sextant biopsy. To reduce the possibility of missed lesions before and after the intervention, we will perform HRA-guided sextant biopsy routinely. In this study, a sextant biopsy is defined as at least 6 biopsies in all directions, regardless of abnormal findings under HRA. The primary outcome is the recurrence rate at 6 months, and the secondary outcomes are the adverse event and recurrence rates at 3 months. Conclusion: This pilot study will provide data on the effectiveness and safety of electrocautery ablation as a treatment for grade 2 or 3 AIN.